2017
DOI: 10.1016/j.jgr.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor kappa-B- and activator protein-1-mediated immunostimulatory activity of compound K in monocytes and macrophages

Abstract: BackgroundCompound K (CK) is a bioactive derivative of ginsenoside Rb1 in Panax ginseng (Korean ginseng). Its biological and pharmacological activities have been studied in various disease conditions, although its immunomodulatory role in innate immunity mediated by monocytes/macrophages has been poorly understood. In this study, we aimed to elucidate the regulatory role of CK on cellular events mediated by monocytes and macrophages in innate immune responses.MethodsThe immunomodulatory role of CK was explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…HEK293 cells were seeded at 1.2 × 10 4 cells per well in 24-well plates. After 24 h, cells were transfected with β-galactosidase and AP-1-Luc for 24 h. The transfection reagent used was PEI as reported previously [ 52 ]. The cells were treated with EGCG for 24 h. Luciferase assay was conducted using the Luciferase Assay System.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293 cells were seeded at 1.2 × 10 4 cells per well in 24-well plates. After 24 h, cells were transfected with β-galactosidase and AP-1-Luc for 24 h. The transfection reagent used was PEI as reported previously [ 52 ]. The cells were treated with EGCG for 24 h. Luciferase assay was conducted using the Luciferase Assay System.…”
Section: Methodsmentioning
confidence: 99%
“…Src undergoes intermolecular autophosphorylation at tyrosine 416, and its phosphorylation promotes the kinase activity of Src, which in turn leads to the phosphorylation of p85 [41]. Western blot assay data demonstrated that the phosphorylated forms of NF-κB pathway-related proteins, such as Src, were decreased by Pg-EE at short (2, 3, and 5 min) and longer time points (5,15,30, and 60 min). Therefore, we can conclude that Src is the target of Pg-EE, and the inhibition of Src kinase results in the reduced activation of proteins downstream of Src.…”
Section: Regulatory Mechanism Of Pg-ee In Nf-κb Pathwaysmentioning
confidence: 97%
“…After 6 h of induction, the total RNA was extracted using TRIzol reagent. cDNA was synthesized from 1 µg of total RNA using MuLV reverse transcriptase, as described previously [30]. The total RNA and synthesized cDNA were also obtained from stomach tissues of HCl/EtOH-induced gastritis mice.…”
Section: Mrna Analysis By a Quantitative Reverse Transcriptase-polymementioning
confidence: 99%
“…For the luciferase reporter gene assay, HEK293 cells (1.0 × 10 5 cells/well in 24-well plates) were transfected with 0.8 μg/mL of plasmids driving the expression of β-galactosidase, AP-1-luc, Col1A1-luc, and FLAG-Smad3. Cells were transfected using the polyethyleneimine (PEI) method [27] and then incubated for 24 h. Finally, HEK293 cells were 2…”
Section: Plasmid Transfection and Luciferase Reporter Gene Assaymentioning
confidence: 99%